Assessing the Safety and Efficacy of Regional Anesthesia for Lower Extremity Microvascular Reconstruction: Enhancing Recovery - Ruan, Qing Zhao; Diamond, Shawn; Zimmer, Scott; Iorio, Matthew L. (Journal of Reconstructive Microsurgery, 2018)
Background Perioperative pain, increased sympathetic tone, and peripheral vasospasm may be safely managed with regional nerve blockade during microvascular reconstruction in the lower extremity. Limited reports exist in this setting; therefore, we evaluated our use of peripheral nerve catheters (PNCs) during microvascular limb salvage to determine safety and efficacy for both patient and flap.Methods A single-institution, retrospective review of a prospectively maintained database on all patients with lower extremity free tissue transfers between 2012 and 2017 was completed. Patients were matched into groups based on PNC utilization. The use of intravenous narcotics including patient-controlled analgesia (PCA), oral narcotics, antiemetics, length of stay (LOS), associated pain scores, flap-related performance, and patient morbidity was recorded.Results Of 48 patients who underwent lower extremity free tissue transfer, 35 satisfied criteria for comparison. Of these, PNC was utilized in 83%. The mean pain score in the immediate postoperative period was 3.84 ± 2.47 (10-point Likert scale). PCA and narcotic use were decreased in the PNC group, and no adverse effects of the catheter were identified. Microsurgical outcomes were not adversely affected in comparison.Conclusion PNC utilization for lower extremity free flap transfer significantly reduced concurrent narcotic use and attained a shorter LOS. The technique provided for safe analgesia during lower extremity free flap reconstructions satisfying the microsurgeon and the anesthesiologist.
Keywords: lower extremity reconstruction; microsurgery; peripheral nerve block; free flap; nerve catheter